Cataract Disease Diagnostic Expert System Using Forward Chaining Method - Firnando, Delvin; Asnawati, Asnawati; Suryana, Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Cataracts are a disease when the lens of the eye becomes cloudy and cloudy. In general, cataracts develop slowly and are not bothersome at first. However, over time, cataracts will interfere with vision and make the sufferer feel like seeing a foggy window, making it difficult to drive, read, and carry out daily activities. The expert system for diagnosing cataracts at Rafflesia Hospital Bengkulu was created to assist in diagnosing cataract patients by entering the symptoms experienced by the patient. In the process of diagnosing the expert system, a method has been applied as an inference engine that makes it easier to find out the results of the diagnosis, this method is Forward Chaining. Based on the results of the tests that have been carried out, the functionality of the expert system for diagnosing cataracts at Rafflesia Bengkulu Hospital has been running well as expected and can provide information on the results of consultations to determine cataracts.